Clinical use of HD-MTX monotherapy in a rare case of refractory primary bone diffuse large B-cell lymphoma with long-term survival after local radiotherapy: A case report - Wu, Zhiya; Teng, Yue; Wu, Jianqiu; Zhang, Honglu; Peng, Weiwei; Meng, Cheng; Tang, Weiyan; Feng, Jifeng (Frontiers in Medicine, 2022)
Primary bone diffuse large B-cell lymphoma (PB-DLBCL) has been rarely reported because of its low incidence. The optimal treatment plan for patients with relapsed/refractory PB-DLBCL remains controversial. In this study, we present a case of a 57-year-old patient with refractory PB-DLBCL to better understand this disease. The patient developed lumbosacral/low extremity pain. A lumbar magnetic resonance imaging (MRI) revealed skeletal lesions with osteolysis in L4-L5 and S1. With the failure of multi-line chemotherapy, the patient developed paralysis of both lower limbs. 18-Fluorinefluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and MRI showed new lesions in the femoral head, cervical and thoracic vertebrae. We tried to treat the patient with adjuvant radiotherapy and 10 courses of high-dose methotrexate (HD-MTX)-based monotherapy, after which the patient was able to walk and achieved complete remission (CR). To the best of our knowledge, this is the first attempt to use local radiotherapy combined with an HD-MTX regimen successfully for the treatment of refractory PB-DLBCL.